Identifikasi Laktoferin Pada Susu Kambing Kacang Dengan Metode Imunodifusi Radial Tunggal Dan Natrium Dodesil Sulfat Poliakrilamida Elektroforesis Gel - Rarah Ratih Adjie Maheswari; Joni Setiawan; Slamet Mulyanto; Imas Batubara; Cece Sumantri; Akhmad Farajallah (Jurnal Ilmu Pertanian Indonesia, 2007)
Kacang goat is one of Indonesian local goat which has not been optimized in exploration. Kacang goat has potency as a dairy goat. Milk and colostrum from this type of goat is one of lactoferrin sources which has various benefit, such as antimicrobial activity. The milk as a lactoferrin source is expected to be a solution for bacterial 9astrointestinal infection cases which is a major problem in Indonesia. This research described the identification of lactoferrin from milk and colostrum of kacang goat by single radial immunodiffusion (SRID) and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). SRID is based on the diffusion of whey protein from a circular well into a homogeneous gel containing anti-lactoferrin. SDS-PAGE was performed in 7.5%  polyacrylamide gel. Both methods were able to identify lactoferrin in colostrum and milk from the sample, but SRID showed low sensitivity toward low concentration of lactoferrin in both colostrums and milk. The estimation of lactoferrin molecular weight by relative mobility of protein from the bands that perform of colostrum and milk of kacang goat is approximately 74,100 Dalton. Based on the ring diameter of the precipitin, the lactoferin level in colostrum and milk increased until 48 hours after postpartum and subsequently decreased. Keywords: colostrum, milk, kacanggoat, lactoferrin, SRID, SDS-PAGE